Treating childhood and adolescent anxiety : a guide for caregivers - Lebowitz, Eli R.; Omer, Haim. (Hoboken, New Jersey : Wiley, 2013)
""Lebowitz and Omer have taken the latest and most relevant scientific research and synthesized it into an essential read for caregivers of anxious children. Treating Childhood and Adolescent Anxiety: A Guide for Caregivers provides an 'inside look' at the nuts and bolts of cognitive behavioral therapy (CBT) for childhood anxiety-the treatment of choice among leading researchers and experts. The book is filled with analogies, examples, and practical advice that professionals and parents will refer back to over and over again.""--Candice A. Alfano, PhD; Director, Sleep and Anxiety.
Preface -- Introduction -- Anxiety disorders of children and adolescents -- Anxiety and emotion regulation -- When anxiety takes over : family accommodation -- Cognitive tools for treating anxiety -- Appendices -- Author index -- Subject index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Anxiety in children; Anxiety in adolescence; Anxiety -- Treatment; Anxiety -- Treatment; Anxiety in adolescence; Anxiety in children; HEALTH & FITNESS -- Children's Health; MEDICAL -- Pediatrics; Anxiety in adolescence; Anxiety in children; Anxiety -- Treatment; Electronic books